PCCs, neo-liberal hegemony and democratic policing. Issue 1 (7th January 2014) - Turner, Liz
Abstract : Purpose: – This paper aims to explore the recent introduction of directly elected police and crime commissioners (PCCs) in England and Wales, and to consider to what extent this new innovation should be considered as a positive contribution to the achievement of democratic policing. Design/methodology/approach: – The paper draws on a range of key sources of academic literature on police accountability and the sociology of policing, as well as considering the content of government pronouncements and legislation. Findings: – The central argument of the paper is that the introduction of PCCs needs to be examined within the context of the hegemony of neo-liberal logic in public services reform. It is argued that some enduring myths of policing, including the myth that the police impartially uphold an impartial law, lend themselves to the depoliticisation of policing which is necessary in order to facilitate neo-liberal colonisation of the service, which is inimical to democratic policing. Originality/value: – The paper builds upon and contests some of the early critiques of the introduction of PCCs which have emerged and proposes a new direction for the development of critique in this area. It will be of interest to policing scholars as well as anyone concerned about the relationship between democracy and policing under current conditions of deep public service cuts and the colonisation of service provision by neo-liberal values.